Metal composite material and preparation method thereof

By combining the metal mesh with the ceramic matrix, the problems of poor bonding effect and low heat resistance when connecting ceramics and metals are solved, low-cost and efficient preparation of metal/ceramic composite materials are achieved, and the firmness of the material is improved and yield rate.

CN119390461APending Publication Date: 2025-02-07PENGLAI SUPERHARD COMPOSITE MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411514608.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

When connecting ceramics and metals, there are problems such as poor bonding effect, concentrated stress, low heat resistance, poor corrosion resistance and high assembly requirements, and the existing connection process is high and the production efficiency is low.

Method used

The metal mesh made of metal wire is combined with the ceramic matrix. The ceramic matrix is ​​made of prepared ceramic powder fired at a lower temperature. The metal mesh is located in the ceramic matrix for interfering with electromagnetic waves. Through simple preparation technology and low cost The sintering process forms a metal/ceramic composite material.

Benefits of technology

The firm connection between ceramics and metals is achieved, the manufacturing cost is reduced, the yield is improved, the problem of ceramic matrix cracking caused by mismatch in thermal expansion coefficients is avoided, and the damage to the material is reduced during sintering and cooling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390461A_ABST
    Figure CN119390461A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of metal composite materials, and particularly relates to a metal composite material and a preparation method thereof. The metal composite material is formed by compounding a metal net and a ceramic matrix, and the ceramic matrix is formed by pressing ceramic powder into a green body. When the green body is pressed, the metal net is pre-buried in the green body, and the metal net and the ceramic base body are firmly compounded together after sintering. The preparation method has the remarkable advantages of being simple in process, low in manufacturing cost and high in finished product rate, and the prepared metal composite material has excellent comprehensive performance. Compared with a resin-based material, the metal composite material has excellent high temperature resistance and aging resistance, and can be used for a long time at 600 DEG C without performance degradation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal composite materials, and particularly relates to a metal composite material and a preparation method thereof. Background Art

[0002] Ceramic materials have many advantages such as high temperature resistance, high strength, high hardness, corrosion resistance and wear resistance, and are widely used in aerospace, power electronics, energy and transportation. However, due to the brittleness of ceramics themselves, their processing performance is poor, and it is difficult to make components with large size and complex shape, which limits their further application and development. Metal materials have excellent room temperature strength, ductility, electrical conductivity and thermal conductivity, and form an obvious complementary relationship with ceramic materials in terms of performance. By combining the two materials, we can make full use of their respective excellent properties to produce engineering materials that meet the requirements. Since ceramics and metals have different bond types and poor surface wettability, how to connect the two in a convenient, low-cost, and firm and tight manner is a problem that needs to be solved.

[0003] At present, the methods for connecting ceramics and metals include mechanical connection, adhesive connection, brazing connection, solid phase diffusion connection, instantaneous liquid phase connection, melting welding, self-propagating high temperature synthesis connection, friction welding, microwave connection, ultrasonic connection, etc. If the ceramic material and the metal material are directly bonded by an adhesive, the bonding effect is not very good; if the two are mechanically connected, a large stress will be generated at the joint; the joint strength of direct brazing is limited, the heat resistance is low, the corrosion resistance is poor, and the assembly requirements are high; the process of metallizing ceramics first and then indirectly brazing is more complicated and costly, and the difference in thermal expansion coefficients between ceramics and metals, ceramic surface pretreatment and equipment requirements must be considered; the connection temperature required for solid phase diffusion connection is higher, the time is longer, the connection needs to be in vacuum, which increases the cost, and there are certain restrictions on the size of the composite material; the production efficiency of instantaneous liquid phase welding is low, and the requirements for preparation and assembly are high; the process parameters of melting welding connection are difficult to control and the equipment is expensive; the burning time of the self-propagating high temperature synthesis connection solder is difficult to control, and the interface reaction control is difficult. Summary of the invention

[0004] In view of the above problems, the present invention provides a metal composite material and a preparation method thereof. The composite material is formed by compounding a mesh woven by metal wires (hereinafter referred to as "metal mesh") and a ceramic matrix, wherein the ceramic matrix is ​​formed by firing prepared ceramic powder at a relatively low temperature; the metal mesh is located in the ceramic matrix and is used to interfere with electromagnetic waves entering the ceramic matrix; the preparation process of the present invention is simple, the manufacturing cost is low, and the yield of finished products is high.

[0005] The first object of the present invention is to provide a metal composite material, which is composed of a metal mesh woven with metal wires and a ceramic matrix. The ceramic matrix is ​​formed by firing prepared ceramic powder at a relatively low temperature. The metal mesh is located in the ceramic matrix and is used to interfere with electromagnetic waves entering the ceramic matrix.

[0006] Furthermore, the ceramic powder comprises the following components: quartz sand, albite, potassium feldspar, borax, talc and zinc oxide.

[0007] The second object of the present invention is to provide a method for preparing the above-mentioned metal composite material, comprising the following steps:

[0008] (1) Cut the metal mesh to a suitable size for future use;

[0009] (2) firstly prepare quartz sand, sodium feldspar, potassium feldspar, borax, talc powder and zinc oxide in a weight ratio of (50-70):(2-4):(2-4):(16-24):(8-12):(3-5), and then add calcium carbonate;

[0010] (3) using a ball mill to ball-mill the raw materials prepared in step (2) to obtain a mixed dry material with a particle size of less than 5 μm;

[0011] (4) adding water to the mixed dry material of step (3), and continuing ball milling to obtain a mixed wet material;

[0012] (5) pouring the mixed wet material of step (4) into a metal mold, and burying the metal mesh cut in step (1);

[0013] (6) molding the mixed wet material in the metal mold of step (5) to obtain a ceramic body;

[0014] (7) placing the ceramic body molded in step (6) into a drying oven for drying;

[0015] (8) placing the ceramic body dried in step (7) into a high-temperature furnace heated to 750-800° C. and keeping the temperature in an air atmosphere;

[0016] (9) Cooling the high-temperature furnace after the insulation in step (8) to below 100° C. to obtain a metal composite material.

[0017] Furthermore, in the step (2), the weight percentage of calcium carbonate is 3-5%.

[0018] Furthermore, in the step (4), the weight percentage of water in the mixed wet material is 6 to 10%.

[0019] Furthermore, in the step (6), the molding pressure is 3 to 5 MPa.

[0020] Furthermore, in the step (7), the drying temperature is 85-95° C. and the drying time is 90-150 min.

[0021] Furthermore, in the step (8), the insulation time is 20 to 30 minutes.

[0022] Furthermore, in the step (9), the cooling rate of the high temperature furnace is 4-6°C / min.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. By using the mixture prepared in the proportion described in step (2), the green body described in step (6) can have two characteristics: 1) when the temperature is lower than 700°C, the green body is in a solid state, and since the temperature is not high, the green body basically does not change in volume; 2) when the temperature is higher than 700°C, the green body will melt, especially at 750-800°C, the green body will melt into a viscous and continuous whole, but still does not change in volume.

[0025] Theoretically, the green body will be accompanied by severe volume shrinkage when it melts. An appropriate amount of calcium carbonate is added to the mixture of the present invention. Since calcium carbonate will decompose at 700-760°C, the carbon dioxide generated by the decomposition of calcium carbonate will gather in the molten green body, causing the molten green body to expand in volume like a balloon, thereby offsetting the volume shrinkage caused by the melting of the green body. After repeated experiments, the present invention determines the weight percentage of calcium carbonate in the mixture to be 3-5%, and by adjusting the sintering temperature, the green body is kept in volume after melting, thereby solving the problem of cracking of the ceramic matrix due to the mismatch of the thermal expansion coefficients of the metal mesh and the green body during high-temperature sintering.

[0026] 2. When conventionally preparing ceramic materials by sintering, a relatively low heating rate is usually used to prevent the green body from cracking during the heating process. Generally, as the temperature rises, the metal material will expand in volume, while the green body will shrink in volume. In the present invention, if a relatively low heating rate is used, the heating rates of the green body and the metal mesh inside it are almost the same. Before the green body melts, the expansion rate of the metal mesh is much greater than that of the green body, and the green body will be "cracked" by the metal mesh.

[0027] In step (8) of the present invention, the green body is directly placed in a high-temperature furnace that has been heated to 750-800°C for sintering. The advantage of this is that the green body will be heated to 750-800°C and melt in a very short time. Due to the hysteresis of heat conduction, the heating rate of the metal mesh in the green body is relatively low. Until the green body is about to melt, the stress generated by the expansion of the metal mesh is not enough to "crack" the green body. Furthermore, after the green body melts, no matter how the metal mesh expands, it is impossible to "crack" the molten green body.

[0028] In addition, when the temperature is lower than 700°C, the volume change rate of the green body pressed by the mixture provided by the present invention is very small, and rapid heating will basically not cause cracks in the green body. Even if rapid heating does cause cracks in the green body, the cracks will heal themselves after the green body melts.

[0029] Therefore, in step (8) of the present invention, the green body is directly placed in a high-temperature furnace that has been heated to 750-800°C for sintering. The original purpose is to avoid cracks in the green body during the heating process and to increase the sintering rate of the material. The benefit brought by this is that the long heating process is eliminated, which greatly reduces the manufacturing cost of the material.

[0030] In addition, in step (8) of the present invention, the sintering temperature used is only 750-800° C., the holding time is only 20-30 minutes, and the sintering atmosphere is air which is very easy to achieve, which can further reduce the manufacturing cost of the material.

[0031] 3. After the composite material is fired, when the temperature drops below 700°C during the cooling process, the ceramic matrix will change from a molten state to a solid state. When the cooling rates of the metal mesh and the ceramic matrix are the same, the ceramic matrix will not be damaged at this time because the shrinkage rate of the metal mesh is higher than that of the ceramic matrix. However, if the furnace temperature drops too quickly, due to the hysteresis of heat conduction, the cooling rate of the metal mesh will be much lower than that of the ceramic matrix, so that the shrinkage rate of the metal mesh is lower than that of the ceramic matrix, which will also cause the ceramic matrix to be "cracked" by the metal mesh.

[0032] It can be seen that the cooling rate of the metal / ceramic composite material prepared by the present invention after sintering should be as low as possible. However, too low a cooling rate will seriously increase the manufacturing cost of the material. In order to take into account both the yield rate and the manufacturing cost of the material, through repeated experiments, it was finally determined that the cooling rate of the metal composite material in step (9) of the present invention is 4-6°C / min. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a process flow chart of this application. DETAILED DESCRIPTION

[0034] The principles and features of the present invention are described below with reference to examples and drawings. Figure 1 A process flow chart of the present application is given.

[0035] Example 1

[0036] A method for preparing a metal composite material comprises the following steps:

[0037] (1) Cut the metal mesh into a size of 160 mm × 160 mm for later use;

[0038] (2) preparing quartz sand, albite, potassium feldspar, borax, talc and zinc oxide in a weight ratio of 50:2:2:16:8:3, and then adding calcium carbonate, wherein the weight percentage of calcium carbonate is 3%;

[0039] (3) using a ball mill to ball-mill the raw materials prepared in step (2) to obtain a mixed dry material with a particle size of less than 5 μm;

[0040] (4) adding water to the mixed dry material of step (3), and continuing ball milling to obtain a mixed wet material, wherein the weight percentage of water in the mixed wet material is 10%;

[0041] (5) pouring the mixed wet material of step (4) into a metal mold, and embedding the metal mesh numbered S-190 cut in step (1) into the mixed wet material;

[0042] (6) molding the mixed wet material in the metal mold of step (5) at a molding pressure of 3 MPa to obtain a ceramic body;

[0043] (7) placing the molded ceramic body of step (6) in a drying oven and drying at 85° C. for 150 min;

[0044] (8) placing the ceramic body dried in step (7) into a high-temperature furnace heated to 800° C. and keeping the temperature in an air atmosphere for 20 minutes;

[0045] (9) Cooling the high-temperature furnace after the insulation in step (8) to below 100° C. at a rate of 6° C. / min to obtain a metal composite material.

[0046] Example 2

[0047] A method for preparing a metal composite material comprises the following steps:

[0048] (1) Cut the metal mesh into a size of 160 mm × 160 mm for later use;

[0049] (2) preparing quartz sand, albite, potassium feldspar, borax, talc and zinc oxide in a weight ratio of 70:4:4:24:12:5, and then adding calcium carbonate, wherein the weight percentage of calcium carbonate is 4%;

[0050] (3) using a ball mill to ball-mill the raw materials prepared in step (2) to obtain a mixed dry material with a particle size of less than 5 μm;

[0051] (4) adding water to the mixed dry material of step (3), and continuing ball milling to obtain a mixed wet material, wherein the weight percentage of water in the mixed wet material is 8%;

[0052] (5) pouring the mixed wet material of step (4) into a metal mold, and embedding the metal mesh numbered S-090 cut in step (1) into the mixed wet material;

[0053] (6) molding the mixed wet material in the metal mold of step (5) at a molding pressure of 5 MPa to obtain a ceramic body;

[0054] (7) placing the ceramic body molded in step (6) into a drying oven and drying at 95° C. for 90 min;

[0055] (8) placing the ceramic body dried in step (7) into a high-temperature furnace heated to 780° C. and keeping the temperature in an air atmosphere for 25 minutes;

[0056] (9) Cooling the high-temperature furnace after the insulation in step (8) to below 100° C. at a rate of 5° C. / min to obtain a metal composite material.

[0057] Example 3

[0058] A method for preparing a metal composite material comprises the following steps:

[0059] (1) Cut the metal mesh into a size of 160 mm × 160 mm for later use;

[0060] (2) preparing quartz sand, albite, potassium feldspar, borax, talc and zinc oxide in a weight ratio of 60:3:3:20:10:4, and then adding calcium carbonate, wherein the weight percentage of calcium carbonate is 5%;

[0061] (3) using a ball mill to ball-mill the raw materials prepared in step (2) to obtain a mixed dry material with a particle size of less than 5 μm;

[0062] (4) adding water to the mixed dry material of step (3), and continuing ball milling to obtain a mixed wet material, wherein the weight percentage of water in the mixed wet material is 6%;

[0063] (5) pouring the mixed wet material of step (4) into a metal mold, and embedding the metal mesh numbered S-052 cut in step (1) into the mixed wet material;

[0064] (6) molding the mixed wet material in the metal mold of step (5) at a molding pressure of 4 MPa to obtain a ceramic body;

[0065] (7) placing the ceramic body molded in step (6) into a drying oven and drying at 90° C. for 120 min;

[0066] (8) placing the ceramic body dried in step (7) into a high-temperature furnace heated to 750° C. and keeping the temperature in an air atmosphere for 30 minutes;

[0067] (9) Cooling the high temperature furnace after the insulation in step (8) to below 100° C. at a rate of 4° C. / min to obtain a metal composite material.

[0068] Example 4

[0069] A method for preparing a metal composite material comprises the following steps:

[0070] (1) Cut the metal mesh into a size of 160 mm × 160 mm for later use;

[0071] (2) preparing quartz sand, albite, potassium feldspar, borax, talc and zinc oxide in a weight ratio of 50:2:2:16:8:3, and then adding calcium carbonate, wherein the weight percentage of calcium carbonate is 3%;

[0072] (3) using a ball mill to ball-mill the raw materials prepared in step (2) to obtain a mixed dry material with a particle size of less than 5 μm;

[0073] (4) adding water to the mixed dry material of step (3), and continuing ball milling to obtain a mixed wet material, wherein the weight percentage of water in the mixed wet material is 10%;

[0074] (5) pouring the mixed wet material of step (4) into a metal mold, and successively burying the metal meshes numbered S-090 and S-290 cut in step (1) into the mixed wet material;

[0075] (6) Molding the mixed wet material in the metal mold of step (5) at a molding pressure of 3 MPa to obtain a ceramic body, wherein the spacing between the metal mesh S-090 and the metal mesh S-290 in the ceramic body is 2 to 4 mm;

[0076] (7) placing the ceramic body molded in step (6) into a drying oven and drying at 95° C. for 90 min;

[0077] (8) placing the ceramic body dried in step (7) into a high-temperature furnace heated to 800° C. and keeping the temperature in an air atmosphere for 20 minutes;

[0078] (9) Cooling the high-temperature furnace after the insulation in step (8) to below 100° C. at a rate of 6° C. / min to obtain a metal composite material.

[0079] Example 5

[0080] A method for preparing a metal composite material comprises the following steps:

[0081] (1) Cut the metal mesh into a size of 160 mm × 160 mm for later use;

[0082] (2) preparing quartz sand, albite, potassium feldspar, borax, talc and zinc oxide in a weight ratio of 70:4:4:24:12:5, and then adding calcium carbonate, wherein the weight percentage of calcium carbonate is 4%;

[0083] (3) using a ball mill to ball-mill the raw materials prepared in step (2) to obtain a mixed dry material with a particle size of less than 5 μm;

[0084] (4) adding water to the mixed dry material of step (3), and continuing ball milling to obtain a mixed wet material, wherein the weight percentage of water in the mixed wet material is 8%;

[0085] (5) pouring the mixed wet material of step (4) into a metal mold, and successively burying the metal meshes numbered S-052 and S-190 cut in step (1) into the mixed wet material;

[0086] (6) Molding the mixed wet material in the metal mold of step (5) at a molding pressure of 5 MPa to obtain a ceramic body, wherein the spacing between the metal mesh S-052 and the metal mesh S-190 in the ceramic body is 2 to 4 mm;

[0087] (7) placing the ceramic body molded in step (6) into a drying oven and drying at 85° C. for 150 min;

[0088] (8) placing the ceramic body dried in step (7) into a high-temperature furnace heated to 780° C. and keeping the temperature in an air atmosphere for 25 minutes;

[0089] (9) Cooling the high-temperature furnace after the insulation in step (8) to below 100° C. at a rate of 5° C. / min to obtain a metal composite material.

[0090] Example 6

[0091] A method for preparing a metal composite material comprises the following steps:

[0092] (1) Cut the metal mesh into a size of 160 mm × 160 mm for later use;

[0093] (2) preparing quartz sand, albite, potassium feldspar, borax, talc and zinc oxide in a weight ratio of 60:3:3:20:10:4, and then adding calcium carbonate, wherein the weight percentage of calcium carbonate is 5%;

[0094] (3) using a ball mill to ball-mill the raw materials prepared in step (2) to obtain a mixed dry material with a particle size of less than 5 μm;

[0095] (4) adding water to the mixed dry material of step (3), and continuing ball milling to obtain a mixed wet material, wherein the weight percentage of water in the mixed wet material is 6%;

[0096] (5) pouring the mixed wet material of step (4) into a metal mold, and successively burying the metal meshes numbered S-052 and S-290 cut in step (1) into the mixed wet material;

[0097] (6) Molding the mixed wet material in the metal mold of step (5) at a molding pressure of 4 MPa to obtain a ceramic body, wherein the spacing between the metal mesh S-052 and the metal mesh S-290 in the ceramic body is 2 to 4 mm;

[0098] (7) placing the ceramic body molded in step (6) into a drying oven and drying at 90° C. for 120 min;

[0099] (8) placing the ceramic body dried in step (7) into a high-temperature furnace heated to 750° C. and keeping the temperature in an air atmosphere for 30 minutes;

[0100] (9) Cooling the high temperature furnace after the insulation in step (8) to below 100° C. at a rate of 4° C. / min to obtain a metal composite material.

[0101] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A metal composite material, characterized in that: The composite material is formed by compounding a metal mesh woven by metal wires and a ceramic matrix. The ceramic matrix is ​​formed by sintering prepared ceramic powder. The metal mesh is located in the ceramic matrix.

2. The composite material according to claim 1, characterized in that The ceramic powder comprises the following components: quartz sand, sodium feldspar, potassium feldspar, borax, talcum powder and zinc oxide.

3. A method for preparing the metal composite material according to any one of claims 1 to 2, characterized in that: The steps include: (1) Cut the metal mesh for later use; (2) firstly prepare quartz sand, sodium feldspar, potassium feldspar, borax, talc powder and zinc oxide in a weight ratio of (50-70):(2-4):(2-4):(16-24):(8-12):(3-5), and then add calcium carbonate; (3) ball milling the raw materials prepared in step (2) to obtain a mixed dry material with a particle size of less than 5 μm; (4) adding water to the mixed dry material of step (3), and continuing ball milling to obtain a mixed wet material; (5) pouring the mixed wet material of step (4) into a mold, and burying the metal mesh cut in step (1); (6) molding the mixed wet material in the mold of step (5) to obtain a ceramic body; (7) drying the ceramic body molded in step (6); (8) placing the ceramic body dried in step (7) into a high-temperature furnace heated to 750-800° C. and keeping the temperature in an air atmosphere; (9) Cooling the high-temperature furnace after the heat preservation in step (8) to below 100° C. to obtain a metal composite material.

4. The preparation method according to claim 3, characterized in that: In the step (2), the weight percentage of calcium carbonate is 3-5%.

5. The preparation method according to claim 3, characterized in that: In the step (4), the weight percentage of water in the mixed wet material is 6-10%.

6. The preparation method according to claim 3, characterized in that: In the step (6), the molding pressure is 3 to 5 MPa.

7. The preparation method according to claim 3, characterized in that: In the step (7), the drying temperature is 85-95° C. and the drying time is 90-150 min.

8. The preparation method according to claim 3, characterized in that: In the step (8), the insulation time is 20 to 30 minutes.

9. The preparation method according to claim 3, characterized in that: In the step (9), the cooling rate of the high temperature furnace is 4-6°C / min.